2023
DOI: 10.3390/biomedicines11102671
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Biomarkers in Cystic Fibrosis and Cystic Fibrosis-Related Diabetes in Children: A Literature Review

Anca Daniela Pinzaru,
Cristina Maria Mihai,
Tatiana Chisnoiu
et al.

Abstract: The most common inherited condition that results in death, particularly in those of Caucasian heritage, is cystic fibrosis (CF). Of all the young adults diagnosed with cystic fibrosis, 20% will develop hyperglycemia as a complication, later classified as a disease associated with cystic fibrosis. Impaired insulin secretion and glucose intolerance represent the primary mechanisms associated with diabetes (type 1 or type 2) and cystic fibrosis. Oxidative stress represents the imbalance between oxygen-reactive sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 132 publications
0
2
0
Order By: Relevance
“…Bedowra's research demonstrates that in type 1 diabetes, where the majority of patients were female and the median duration of the disease was 2.5 years, vitamin D deficiency is more prevalent than vitamin D insufficiency [32]. It has been shown that vitamin D insufficiency is more common where most of sample studied were males newly diagnosed with diabetes [33]. Mean serum calcium was on lower normal in both vitamin D deficit and insufficient patients and this is due to not only decrease serum vitamin D but also increase in glucose blood level, resulting in a significant decrease in the concentration of the serum calcium [34].…”
Section: Discussionmentioning
confidence: 99%
“…Bedowra's research demonstrates that in type 1 diabetes, where the majority of patients were female and the median duration of the disease was 2.5 years, vitamin D deficiency is more prevalent than vitamin D insufficiency [32]. It has been shown that vitamin D insufficiency is more common where most of sample studied were males newly diagnosed with diabetes [33]. Mean serum calcium was on lower normal in both vitamin D deficit and insufficient patients and this is due to not only decrease serum vitamin D but also increase in glucose blood level, resulting in a significant decrease in the concentration of the serum calcium [34].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Galiniak et al (2023) explored biomarkers of nitrosative stress in cystic fibrosis, revealing significant findings in the serum of patients, which underscores the complex interplay between oxidative and nitrosative stress in pulmonary diseases. Another study highlights the critical roles of oxidative stress in pulmonary disease progression, further emphasizing the need for detailed investigations into these mechanisms across a range of conditions ( Pinzaru et al, 2023 ).…”
Section: Role Of Oxidative Stress In the Lungmentioning
confidence: 99%